Implementation of Rewards at Pesonna Hotel Malioboro Related to Employee Satisfaction - Kiki Rizki Makiya; Damiasih Damiasih; Cerry Kartika Kwartania; Amri Amirrulloh (International Journal Of Tourism, 2022)
Abstract Employee job satisfaction with the company can affect employee performance. Reward is one aspect that can affect the level of employee satisfaction. HRD Pesonna Hotel Malioboro Yogyakarta is the department responsible for implementing rewards for employees.Purpose: The writing of this article was conducted to determine employee satisfaction with the implementation of giving rewards at Pesonna Hotel Malioboro Yogyakarta.Research methods: Collecting data in the form of participatory observation, in-depth interviews with resource persons related to the research topic, and literature study.Results and discussions: The results obtained are that the application of rewards affects employee satisfaction based on four aspects, which consist of: the work itself, salary, promotion, and leadership.Conclusion: Most employees are satisfied with the application of rewards because there is already an appreciation felt by employees from the company. However, it still needs improvement so that the application of rewards can be maximized